Synthesis and Antioxidant Activity of S-[bis-2-(Chloroethyl)-amino]-4-substituted-6- phenyl Pyrimidine-2-yl-ethanethioate Derivatives with Nitrogen Mustards - Murugan, V.; Geetha, K.M.; Sandhyavali, M.S.; Badami, S. (Asian Journal of Chemistry, 2010)
A series of new chalcones containing pyrimidine heterocyclic ring have been prepared by the condensation of various aldehydes with acetophenone followed by cyclization with thiourea in presence of alcoholic KOH. Chalcones thus prepared were subjected to acetylation with chloroacetyl chloride and the resultant S-chloroacetyl derivatives were subjected to a nucleophilic substitution reaction with diethanolamine by heating under reflux in pyridine. The compounds thus obtained were subjected to a chlorination reaction using phosphorous oxychloride to get title compounds. Compounds prepared were recrystallized from acetone, alcohol and diethyl formamide. All the synthesized compounds were screened for their antioxidant activity by 2,2'-diphenyl-1-picryl hydrazyl and 2,2'-azino bis- 3-ethylbenzothiazoline-6-sulphuric acid methods.